2011
DOI: 10.1137/100809799
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the DPG Method for the Poisson Equation

Abstract: We give an error analysis of the recently developed DPG method applied to solve the Poisson equation and a convection-diffusion problem. We prove that the method is quasioptimal. Error estimates in terms of both the mesh size h and the polynomial degree p (for various element shapes) can be derived from our results. Results of extensive numerical experiments are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
167
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(167 citation statements)
references
References 20 publications
(40 reference statements)
0
167
0
Order By: Relevance
“…In hindsight, we understand that this is the essence of the analysis not only in this paper, but also in [6].…”
Section: The Analysis In Hindsightmentioning
confidence: 73%
See 3 more Smart Citations
“…In hindsight, we understand that this is the essence of the analysis not only in this paper, but also in [6].…”
Section: The Analysis In Hindsightmentioning
confidence: 73%
“…The details of the derivation are very similar to the case of the Poisson equation [6], so we omit them and simply present the DPG weak formulation, after a foreword on notations. Let Note that in the latter definition, complex conjugations are absent, so to match conjugate linearity of other terms, we will often use notations like w,¯ ∂Ω h and w, ∂Ω h , whose meanings are self-explanatory.…”
Section: Application To the Helmholtz Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research topic, we focus on the phenomenon indicated as volume locking which can lead to failure of a numerical method when constraints, as related to incompressible materials, are not accounted properly. In this contribution we firstly introduce the primal discontinuous Petrov-Galerkin (dPG) Finite Element Method (FEM) for linear elasticity based on the novel dPG discretization method proposed recently in [1][2][3]. Therefore, a further primary variable is introduced resulting in a mixed FEM and the interpolation functions for the test space are chosen to be discontinuous.…”
Section: Introductionmentioning
confidence: 99%